Correlation Between Ocular Rigidity With Intraocular Pressure In Patient With Type 2 Diabetes Mellitus - Roland Iqbal; Prima Maya Sari; Ramzi Amin; Fidalia (Sriwijaya Journal of Ophthalmology, 2019)
ABSTRACT Introduction and Objectives: Diabetes mellitus (DM) is known to have a biomechanical effect on tissue. High blood glucose concentrations that lead to increased production of free radical intermediates causes ocular rigidity (OR) changes. This change can effect intraocular pressure (IOP) in patients with type 2 DM. This study to determine correlation between ocular rigidity with IOP in patients with type 2 DM. Methods: A cross-sectional study with a correlation test design of OR with IOP in type 2 DM patients was conducted in RSUP dr. Mohammad Hoesin Palembang from January until June 2018. Eighty eye samples consist of 60 type 2 DM and 20 control group. IOP examination was performed using a Goldmann applanation tonometer and OR measurements using schiotz tonometer with two loads then assessed in Friedenwald differential tables. Result: There was a significant correlation between diabetic retinopathy and OR (p=0,000). There was a significant correlation between OR and IOP in NPDR and PDR group (p=0,000). There was a significant relationship between patient age with OR and IOP (p<0,05). Conclusion: There is a significant correlation between ocular rigidity and IOP in people with type 2 DM.